Problem 4
Find the distance from A to C using the distance formula
d = sqrt((x2-x1)^2+(y2-y1)^2)
d = sqrt((3-(-3))^2+(-1-1)^2)
d = sqrt((3+3)^2+(-1-1)^2)
d = sqrt((6)^2+(-2)^2)
d = sqrt(36+4)
d = sqrt(40)
d = 6.324555
which rounds to 6.3
You have the correct answer for problem 4
=========================================================
Problem 5
The answer is not choice B (you mixed the inverse up with the contrapositive)
The answer is actually choice C
In general, a conditional is in the form "If P, then Q"
The inverse will have us negate the P and Q. They will stay in the same spot and not flip places
So the inverse would be "If not P, then not Q"
This is why the answer is choice C